Stabilisasi Tanah Lempung Dengan Variasi Penambahan Domato - Bleiser Tanari; Irnovia Berliana Pakpahan (Universitas Medan Area, 2023)
One of the ways to improve unstable soil properties is by stabilizing it. Soil stabilization can be done by adding a certain additive to the unstable soil.The objective of this study was to determine the effect of Domatoaddition on clay swelling and shrinkage property and carrying capacity for subgrades. The testing of the physical properties of the original clay soil was caried out.After that, Domato was added to clay soil with variations of 5%, 10%, 20% and 30% of the weight of the original soil.The mechanical properties of the mixture were tested, namely CBR unsoaked, CBR soaked, expansion and free compressive strength. The results showed that the highest increase in the strength of clay stabilized with Domato was in the combination of 70% clay + 30% Domato, namely by increasing the unsoaked CBR value and soaked CBR value by 450% and 655% respectively. The value of the free compressive strength for the 70% clay + 30% Domato mixture combination was 346% of the original soil.